Unregistered Marriage with Wali Muhakkam in Shafi‘i Fiqh Perspective and Indonesian Positive Law - Safitra, Windy; Badri, Khairul (KIPS Institute Bukittinggi, 2026)
This study investigated the practice of nikah siri (unregistered marriage) involving the use of a wali muhakkam in Indonesia from the perspectives of Shafi?i jurisprudence and positive law. The practice had frequently been justified as a theological response to administrative barriers or the refusal of a wali nasab (?adhal). However, it produced significant legal vulnerability for women and children. Employing a qualitative research design, the study adopted a library-based approach and jurisprudential analysis, utilizing content analysis to examine authoritative Shafi?i legal texts alongside Indonesian marriage regulations and judicial decisions. The findings demonstrated that, in the contemporary context marked by extensive access to the Office of Religious Affairs (Kantor Urusan Agama/KUA), the invocation of a wali muhakkam no longer satisfied the requirement of geographical necessity recognized in Shafi?i fiqh. From a legal standpoint, the practice constituted a form of legal circumvention that undermined the authority of the state-appointed wali hakim. Furthermore, the study revealed that Indonesian religious court judges functioned as agents of substantive justice by safeguarding the rights of the wali mujbir through structured mediation mechanisms and rigorous verification procedures. The study concluded that religious legitimacy must be integrated with state legal frameworks to ensure legal certainty and to promote genuine mashlahah within the family institution.